Exercise during pregnancy: knowledge and beliefs of medical practitioners in South Africa: a survey study. Issue 1 (December 2015) - Watson, Estelle; Oddie, Brydie; Constantinou, Demitri
Abstract Background There is compelling evidence for the benefits of regular exercise during pregnancy, and medical practitioners (MPs) can play an important role in changing antenatal health behaviours. The purpose of this study was to assess the knowledge, attitudes and beliefs of South African MPs towards exercise during pregnancy. Methods A convenience sample of ninety-six MPs working in the private health care sector, including General Practitioners (n = 58), Obstetricians/Gynaecologists (n = 33) and other Specialists (n = 5), participated in this cross sectional, descriptive survey study. A 33-item questionnaire was distributed manually at medical practices and via email to an on-line survey tool. Descriptive statistics and frequency tables were calculated for all questions. Chi-squared and Fisher's exact statistical tests were used to determine the differences in response by age, speciality and years of practice (p < 0.05). Results The majority of practitioners (98 %) believe that exercise during pregnancy is beneficial, and were knowledgeable on most of the expected benefits. Seventy-eight percent believed that providing exercise advice is an important part of prenatal care, however only 19 % provided informational pamphlets and few (24 %) referred to exercise specialists. A large majority (83 %) were unaware of the recommended exercise guidelines. Although age and years of practice played no role in this awareness, practitioners who focussed on obstetrics and gynaecology were more likely to be aware of the current guidelines, than those in general practice (p < 0.001). Conclusion Although the MPs were largely positive towards exercise during pregnancy, their advice did not always align with the current guidelines. Therefore, better dissemination of available research is warranted, to bridge the gap between clinical knowledge and current recommendations for physical activity promotion.